AKIBAT HUKUM PEREDARAN MAKANAN DAN MINUMAN OLAHAN ILEGAL DALAM PERSPEKTIF PERLINDUNGAN KONSUMEN - Wahyudi; Aisyah Dinda Dwitami (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
This study was conducted with the aim of determining the legal consequences of illegal circulation of processed food and beverages from the point of view of consumer protection. Processed foods and beverages are widely circulated in modern and traditional market environments, but there are still these products in circulation that do not have a distribution permit. Because the circulation of processed food and beverages does not go through the procedure stage to obtain a distribution permit so that consumers can be harmed. This research was conducted by descriptive analysis using normative juridical approach methods and qualitative juridical data analysis to achieve legal certainty with laws and regulations so that existing provisions do not conflict with each other. The results of this study show that the tendency of the public as consumers of processed food and beverage products, both domestic production and imported products, does not pay attention to the distribution permit from BPOM, so that the product is still widely circulated in traditional and modern markets. The circulation of these products is contrary to BPOM Regulation Number 27 of 2017 concerning Processed Food Registration. As a result of the illegal circulation of processed food and beverages, consumers are not protected from all forms of contents and packaging of the product and consumers risk being harmed if the product is not in accordance with what is stated on the packaging. Legal remedies against aggrieved consumers based on consumer protection laws can file a lawsuit through the Consumer Dispute Resolution Agency.